Evaluation of Trace Element Levels and Microbiological Quality of Borehole and Well Water from Different Sources in Wukari, Taraba State - Chidi, Obasi Blessing; Olawumi, Elegbede Blessing (Darul Yasin Al Sys, 2025)
This study assessed the levels of trace elements and microbiological quality of groundwater sources from boreholes and wells in Wukari. Sampling was conducted at five locations, with five samples each collected from boreholes and wells and analyzed using standard procedures. For borehole samples, trace element concentrations ranged from iron (Fe: 0.0127–0.0145 ppm), chromium (Cr: 0.0014–0.0110 ppm), manganese (Mn: 0.0019–0.0183 ppm), and copper (Cu: 0.0013–0.0155 ppm). Well water samples showed higher variability, with Fe (0.0216–0.6216 ppm), Cr (0.0190–0.1786 ppm), Mn (0.0109–0.0291 ppm), and Cu (0.0101–0.0425 ppm). All samples were within World Health Organization (WHO) permissible limits, except for elevated Fe in sample EPW (0.6216 ppm) and high Cr in samples OMW and EPW (0.1190 ppm and 0.1786 ppm, respectively). Zinc was not detected in any sample. Microbiological analysis revealed aerobic plate counts ranging from 3.1 × 10⁷ to 8.0 × 10⁷ cfu/ml, with no coliform or fungal growth detected. Bacterial isolates included Escherichia coli, Pseudomonas spp., Klebsiella spp., Bacillus spp., Staphylococcus aureus, and Staphylococcus epidermidis, with Klebsiella spp. and E. coli being predominant. While trace element levels suggest that groundwater sources are largely safe for drinking, the presence of potentially pathogenic bacteria highlights the need for appropriate treatment before consumption or use in food processing. These findings underscore the importance of continuous monitoring to safeguard public health and prevent waterborne diseases.